APLIKASI PRINSIP KONSERVASI DALAM PENGELOLAAN HUTAN DAN LAHAN DI KOTA PADANGSIDIMPUAN, PROVINSI SUMATERA UTARA - , ADY SUHENDRA HARAHAP, Prof. Dr. Ir. H. Djoko Marsono ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Some facts destruction of forest and land in the City Padangsidimpuan is occurrence of natural disaster of floods and landslide and forest productivity decline. Problems and conditions of forest and land in the City Padangsidimpuan requires a solution and follow up treatment, especially in improving policy and planning. Data collection to obtain primary data and secondary data to get a picture of aspects of forest and land, aspects of forest resources and land, aspects of policy/institutional and community empowermen aspects. The studies were comprehensive. The study based on aspects of forest area and forest area of land shown Padangsidimpuan City is an area of 1826 ha (12.31% of the size of the city). This can be increased to 30% as mandated by law to plan the allotment of space as forest and / or function as a forest. Based on the aspects of forest resources and forest land from the city known Padangsidimpuan not available so more appropriately directed to the development of environmental services. Community forest management aimed at institutional development of community forests, causing a variety of institutional diversification as a whole will be able to create a forestry agribusiness development.